Annual Plan 1987-88 Government of Mizoram - Planning Commission (Planning Commission, 1987)
The state of Mizoram is in the North Eastern corner of India between Tripura and Bangladesh in the West, Burma in the east and south, in the north it has a boundary with Manipur and Cachar District of Assam Sta te. Mizoram attained, statehood with effect from February 1987 becoming the 24th in the Indian union. Mizoram has an area of 21,081 sq.Kms. with a population of 4,93,757 ( according to 1981 census) most of the areas are covered by sharp ranges interspered with deep gorged terrains.
Planning and Programme Implementation Department Government of Mizoram